Analisis Faktor-Faktor yang Mempengaruhi Kredit Bermasalah di Koperasi Pegawai Negeri (KPN) Susila Bhakti - Kadek Pratama Dharma Yuda; I Nengah Suarmanayasa (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to examine (1) the factors that influence non-performing loans, (2) the most dominant factors influencing non-performing loans and (3) the efforts made to overcome problem loans in the Susila Bhakti Cooperative. The subject in this study was the Civil Servant Cooperative (KPN) Susila Bhakti. The object of this study was members of the Civil Servant Cooperative (KPN) Susila Bhakti Data were collected by questionnaire, and analyzed by factor analysis. The results showed that the factors affecting non-performing loans in the Civil Servant Cooperative (KPN) Susila Bhakti were excessive interference, irregularities in procedures, and lack of oversight from the supervisory body. The most dominant factor influencing non-performing loans is factor 3 with varimax Rotation value of 0.927, which means that the factors affecting non-performing loans are dominated by factor 3 of 0.927, emphasizing the weakness of the debtor's ability.